EPID-28. THE IMPACT OF RITUXIMAB COMBINATION CHEMOTHERAPY ON THE CLINICAL OUTCOMES OF PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA (PCNSL): AN UPDATED META-ANALYSIS - Haddad, Philip (Neuro Oncol, 2020)
BACKGROUND: PCNSL is a rare diffuse large B-cell lymphoma (DLBCL) confined to the central nervous system accounting for approximately 2–5% of all primary brain tumors. Although there is no standard combination of chemotherapy, high-dose methotrexate is considered the backbone of all PCNSL chemotherapy regimens. Rituximab, an anti-CD20 antibody, has been a standard component of DLBCL combinations since it improves progression-free (PFS) and overall survival (OS). However, the role of Rituximab in the treatment of PCNSL has been controversial with contradictory RESULTS: A small meta-analysis conducted in 2019 found no associated survival advantage for Rituximab when added to chemotherapy. However, this meta-analysis was small and included only 2 studies. The purpose of this updated meta-analysis is to evaluate in a more comprehensive way the impact of Rituximab combination chemotherapy on the clinical outcomes of patients with PCNSL incorporating all available comparative studies. METHODS: A review of the medical literature was conducted using online databases. Inclusion criteria consisted of PCNSL diagnosis, English language, and studies reporting OS and PFS with hazard ratios (HR) or Kaplan-Meier curves that compared similar regimens with and without Rituximab. A meta-analysis using an inverse variance method with a random-effects model was conducted. RESULTS: Four comparative studies with a total of 467 patients were included in this meta-analysis. Two of these studies were retrospective comparative studies and two were randomized phase II trials. When added to chemotherapy, Rituximab was found to significantly improve the OS and PFS (HR(OS) 0.75, 95%CI: 0.59–0.96, p=0.02; HR(PFS) 0.67, 95%CI: 0.53–0.85, p=0.001) with a heterogeneity estimate, I(2)=0%. CONCLUSIONS: This is the first meta-analysis to show that adding Rituximab to chemotherapy is associated with OS and PFS in patients with PCNSL. In the absence of randomized clinical trials, this meta-analysis represents the most compelling data supporting the routine use of Rituximab combinations in PCNSL.